A Life Course Perspective on Chinese Youths From the Transformation of Social Policies to the Individualization of the Transition to Adulthood - Constantin, Sandra V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
This open access book investigates from a life-course perspective the individualization process and the challenges faced by young adults in post-collectivist China, where people are enjoined to "liberate" (jiefang) their individual capacities, to "rely on themselves" (kao ziji) and to no longer "depend on the state" (kao guojia). Based on unique quantitative and qualitative data, this book provides a solid empirical portrait of Chinese youths and transformation of social policies in post-collectivist China This book will be a great resource to students, academics as well as social scientists and policy-makers who wish not only to understand how, in such a short period of time, young adults and their families have managed to navigate from a relatively egalitarian society to one of the most unequal, but also how the articulation between socialist and neoliberal ideologies is reconfiguring social and economic relations as well as women$1 (Bs and men$1 (Bs life-course. The basis of the English translation of this book from its French original manuscript was done with the help of artificial intelligence. A subsequent human revision and rewriting of the content was done by the author.s
Preface -- Acknowledgements -- Chapter 1: Introduction -- Part 1: Revisiting individualization in China through the prism of the transition to adulthood: Chapter 2: Institutionalized individualism in post-collectivist China -- Chapter 3: Suzhi discourse as a structural component of institutionalized individualism in post-Maoist China -- Chapter 4: A life-course perspective on the individualization process in post-collectivist China -- Part 2: Coming of age in uncertain times: Chapter 5: Exploring pathways to adulthood -- Chapter 6: The rise of new social risks in post-collectivist China -- Part 3: The rise of neo-familialism: Chapter 7: The postponement of family formation due to employment instability -- Chapter 8: Young adults$1 (Baspiration for intimacy in post-collectivist China -- Chapter 9: What does the individualization process do to intergenerational solidarities? -- Conclusion -- Appendix.s
Keywords: Life cycle, Human; Population -- Economic aspects; Sociology; Social groups; Life Course; Population Economics; Sociology of Family, Youth and Aging